A Field Study For Designing An Integrated Framework To Enhance Information Security In The E-Management Environment - Abdo, Shuaib Mohammed Sharif; Hameed, Asmaa Rasheid (Academia Open, 2026)
General Background: The expansion of digital transformation in governmental institutions has increased reliance on electronic management systems, making information security a strategic priority. Specific Background: Despite the adoption of global standards such as ISO 27001, NIST, COBIT, and Zero Trust, existing approaches often separate technical and administrative dimensions, limiting practical implementation in e-management environments. Knowledge Gap: There remains a lack of a unified framework integrating technological, governance, and human-cultural aspects tailored to institutional contexts. Aims: This study develops an integrated information security framework combining technical infrastructure, governance policies, training, and security culture using Design Science Research Methodology. Results: Empirical analysis using SEM-PLS shows that organizational maturity (β=0.67) and technical measures (β=0.59) are primary drivers, while policies and training (β=0.44) and security culture (β=0.18) play supporting and mediating roles, explaining 74% of variance. Implementation increased readiness index from 65.2 to 83.9 and reduced incidents by 31%. Novelty: The study proposes a holistic, empirically validated framework integrating technical, administrative, and cultural dimensions within a single architecture. Implications: The framework provides actionable guidance for policymakers to establish unified governance structures, strengthen security culture, and deploy adaptive mechanisms in electronic management systems. Highlights: • Holistic Model Integrates Governance Structures With Technological Safeguards and Human Factors • Empirical Evidence Explains Major Variance in System Protection Performance • Framework Application Shows Measurable Increase in Readiness and Reduced Incident Frequency Keywords: Information Security, E-Management, Cybersecurity Framework, Security Culture, Organizational Maturity